Association between postural tremor and risk of disability in community‐dwelling older people. Issue 4 (3rd December 2022) - Xu, Xitong; Chen, Jie; Ji, Shaozhen; Gu, Zhuqin; Chen, Meijie; Chhetri, Jagadish Kumar; Chan, Piu
Abstract: Background: The prevalence of postural tremor increases with age and the tremor has been found to be associated with aging‐related physiological decline. However, whether postural tremor in older adults is associated with adverse outcomes such as disability is unclear. This study investigated the association between postural tremor and the risk of disability in activities of daily living (ADL) among community‐dwelling older people. Methods: Data were derived from a population‐based study of Chinese adults aged ≥55 years. Postural tremor was assessed at baseline using a two‐step method (i.e., tremor screening followed by examination of positive cases). ADL disability was determined using an 8‐item questionnaire, which covered the mobility and self‐care domains of ADL. Participants free of ADL disability at baseline were followed for up to 4 years. Results: The prospective analyses included 5868 participants. Participants with postural tremor were at greater risk of incident ADL disability, particularly disability in the mobility domain of ADL. After multivariate adjustment, postural tremor was not significantly associated with incident ADL disability (multivariate‐adjusted relative risk [RR] = 1.05, 95% confidence interval [CI] = 0.77–1.43), and was marginally associated with incident disability in the mobility domain of ADL (multivariate‐adjusted RR = 1.36, 95% CI = 0.98–1.88). The risk of mobility‐related ADL disability was significantly increased among men, but not women, with postural tremor (multivariate‐adjusted RR = 1.84, 95% CI = 1.11–3.05). Older age and an increased number of chronic comorbidities mainly explained the higher risk of ADL disability in older people with postural tremor. Conclusions: Postural tremor in older adults is associated with greater incidence of ADL disability, particularly mobility‐related ADL disability. The association is largely due to older age and a higher prevalence of chronic comorbidities in older people with postural tremor. Postural tremor is not a strong independent predictor of ADL disability in older people.